Unraveling aromaticity: the dual worlds of pyrazole, pyrazoline, and 3D carborane - Zahra Noori; Miquel Solà; Clara Viñas; Francesc Teixidor; Jordi Poater (Beilstein Journal of Organic Chemistry)
A new series of o-carborane-fused pyrazoles has been recently successfully synthesized. This fusion was expected to create a hybrid 3D/2D aromatic system, combining the 3D aromaticity of o-carborane with the 2D aromaticity of pyrazole. However, while the boron cage retains its aromatic character, the pyrazole’s aromaticity is lost. As a result, rather than forming o-carborane-fused pyrazoles, the synthesis yielded o-carborane-fused pyrazolines, which are non-aromatic. The limited overlap between the π molecular orbitals (MOs) of the planar heterocycle and the n + 1 MOs of the carborane prevents significant electronic delocalization between the two fused components. This contrasts with the fusion of pyrazole and benzene to form indazole, where both rings maintain their 2D aromaticity. Our findings demonstrate that the peripheral σ-aromaticity of carborane and the π-aromaticity of the heterocycle are orthogonal, making a true 3D/2D aromatic system unachievable. The carborane is highly aromatic, generating highly negative NICS values (−25 to −30 ppm). We have observed that these high NICS values extend to fused rings, leading to incorrect estimations of aromaticity. Therefore, relying solely on NICS can be misleading, and other computational indicators, along with experimental or structural data, should be used to accurately assess aromaticity.